Conflictividad genérica y fuentes orales para la historia antigua - Cascajero, Juan (Gerión. Revista de Historia Antigua, 2001)
Only the permanent conscience, in women and men, of the negative discrimination (past and present) it can justify and to impel, for the sake of the equality, the woman’s absolutely indispensable positive discrimination in the daily life, in the politics... and in the historiography. The remains of the ancient orality, the oral sources, with the peculiarities and limits from their applicability to the Ancient History, promote that conscience: they allow to think the forms in that it produced, it reproduced and it expresed a generic conflict, mainly characterized for the woman’s oppression-exploitation, on one hand, and the desperate intents of legitimation-justification of the patriarchal domination, for another.